INTEGRASI STRATEGIS PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM OPERASIONAL SATUAN PENDIDIKAN SEBAGAI UPAYA PERSONALISASI PENDIDIKAN DI SEKOLAH DASAR - Ni Kadek Depi Dumaini; Gusti Ayu Nanik Ardhiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research analyzes the synchronization of differentiated learning strategies within the School Operational Curriculum (KOSP) at the elementary school level to support educational personalization. Although Kurikulum Merdeka offers high flexibility, its implementation often remains trapped in administrative formalities. This study employs a qualitative descriptive-analytical approach, collecting data through in-depth interviews with principals and teachers, as well as KOSP documentation analysis. The results reveal a "decoupling" phenomenon, where KOSP documents integrate differentiated strategies only at a textual-macro level without reaching technical operational aspects. Currently, the KOSP provides only passive support and fails to offer legal protection for teachers to perform adaptive instructional innovations. Low managerial coherence and one-way communication between curriculum developers and practitioners act as the primary barriers. To synchronize these policies, this study proposes activating professional learning communities to reposition teachers as curriculum co-developers based on diagnostic assessment data. Ultimately, this transformation redefines the KOSP from a mere administrative artifact into a responsive managerial instrument that addresses student heterogeneity to achieve substantive educational equityThis research analyzes the synchronization of differentiated learning strategies within the School Operational Curriculum (KOSP) at the elementary school level to support educational personalization. Although Kurikulum Merdeka offers high flexibility, its implementation often remains trapped in administrative formalities. This study employs a qualitative descriptive-analytical approach, collecting data through in-depth interviews with principals and teachers, as well as KOSP documentation analysis. The results reveal a "decoupling" phenomenon, where KOSP documents integrate differentiated strategies only at a textual-macro level without reaching technical operational aspects. Currently, the KOSP provides only passive support and fails to offer legal protection for teachers to perform adaptive instructional innovations. Low managerial coherence and one-way communication between curriculum developers and practitioners act as the primary barriers. To synchronize these policies, this study proposes activating professional learning communities to reposition teachers as curriculum co-developers based on diagnostic assessment data. Ultimately, this transformation redefines the KOSP from a mere administrative artifact into a responsive managerial instrument that addresses student heterogeneity to achieve substantive educational equity